Հայաստանի ազգային գրադարանի թվային փոխակերպման գործընթացները արդի մարտահրավերներին ընդառաջ - Մելիքբեկյան Նաիրա / Melikbekyan Naira (Հայաստանի ազգային գրադարան / National Library of Armenia, 2024)
The aim of the publication is to highlight the impact of information technology, virtual reality, artificial intelligence and the achievements in many other fields on libraries in general and, in particular, on the activities of the National Library of Armenia in the face of contemporary challenges. Prioritising the preservation of printed heritage, the library embarked on the mission of digitising its collections and making them accessible to users through Optical Character Recognition (OCR) systems. To achieve the aim, the following objectives have been set: presenting the process of digital transformation of the library, discussing priorities for the digitisation of the national printed heritage, providing access to digital versions in the repositories, outlining the recognition process.
Բանբեր Հայաստանի գրադարանների ։ Գիտամեթոդական էլեկտրոնային հանդես / Գլխավոր խմբագիր` Աննա Չուլյան ; Պատասխանատու խմբագիր՝ Հայկանուշ Ղազարյան ․- Երևան ։ «Գիրք» հրատարակչություն , 2024 ․- N 2 .- էջ 140-147
Keywords: Գրադարանագիտություն, մատենագիտություն և արխիվավարություն